Estudo teórico das propriedades mecânicas e eletrônicas de sistemas bidimensionais do grupo IV sob deformações - Vargas, Douglas Willian Duarte de (2018)
In this work we study two dimensional materials compounds of group IV elements such as graphene, silicene and germanene under biaxial and uniaxial strain. The aim of this study is understand the mechanical properties of these materials and how the strain modify their electronic properties. Using the density functional theory as implemented in the Quantum ESPRESSO (QE) package, we determined the Lamé coefficients and using its coefficients we calculated the elastic constants C11 and C12. The Young modulus in two dimension and the Poisson ratio was obtained via uniaxial strain in two directions: armchair and zigzag. Using the Voigt approximattion we estimated the Bulk modulus and the Shear modulus. All of those values are in good agreement with the literature where graphene is characterized as a stiffness material. We analyzed the stress-strain relation for all of three materials in the elastic region, where was observed an asymmetric behavior in ultimate tensile strength, where the armchair direction is the more stiff. The electronic properties was analyzed under uniaxial strain in three regions: linear (" = 0; 03), harmonic (" = 0; 09), and near to ultimate tensile strength (" = 0; 15). Graphene under strain does not show significant changes in its electronic properties. On the other hand, silicene and germanene show the autodopping behavior, where electrons (tipe n conductivity) or/and holes (tipe p conductivity) appear near to the Fermi level, in the vicinity of the Dirac cone greater than 9%. This way, we showed that strain can control the conductivity properties of silicene and germanene.